2012
DOI: 10.1186/1471-244x-12-174
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ADHD symptoms and global impairment in childhood on working disability in mid-adulthood: a 28-year follow-up study using official disability pension records in a high-risk in-patient population

Abstract: BackgroundIndividuals with ADHD have been associated with more employment difficulties in early adulthood than healthy community controls. To examine whether this association is attributable specifically to disturbance of activity and attention (ADHD) or to psychopathology in general, we wanted to extend existing research by comparing the rate of mid-adulthood working disabilities for individuals diagnosed with ADHD as children with the rate for clinical controls diagnosed with either conduct disorder, emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 67 publications
3
13
0
1
Order By: Relevance
“…In these studies, considerably lower RTW rates were reported for depression compared to anxiety and stress-related disorders in line with the current study. Strikingly low-RTW rates were also found for hyperkinetic disorders (F90) in accordance with a recent Norwegian study, where such disorders were specifically linked to reduced work ability and disability pension [28]. This result may also be due to unaccounted comorbid mental conditions which have been reported to prolong sick leave [25].…”
Section: Discussionsupporting
confidence: 78%
“…In these studies, considerably lower RTW rates were reported for depression compared to anxiety and stress-related disorders in line with the current study. Strikingly low-RTW rates were also found for hyperkinetic disorders (F90) in accordance with a recent Norwegian study, where such disorders were specifically linked to reduced work ability and disability pension [28]. This result may also be due to unaccounted comorbid mental conditions which have been reported to prolong sick leave [25].…”
Section: Discussionsupporting
confidence: 78%
“…In Japan, KK children’s maladjustment during transitional periods is already a national concern [34]. In addition to diagnostic features, poor psychosocial functioning predicts future social and economic exclusion in children with mental health problems [35]. The professionals’ narratives of KK could be considered convincing examples of such poor psychosocial functioning, and hence this study could provide the variables relevant to children in need of early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of onset is between seven and nine (Kessler et al 2007) and 95 % of people affected are diagnosed before 12 years old (Kessler et al 2005). It is highly associated with disability in adulthood, and it causes a substantial economic burden on society, with the 30 % of adult patients receiving a disability pension (Mordre et al 2012).…”
Section: Introductionmentioning
confidence: 99%